2022
DOI: 10.1371/journal.pone.0266137
|View full text |Cite|
|
Sign up to set email alerts
|

Dental follicle mesenchymal stem cells ameliorated glandular dysfunction in Sjögren’s syndrome murine model

Abstract: Objective Dental mesenchymal stem cells (MSCs) are potential for use in tissue regeneration in inflammatory diseases due to their rapid proliferating, multilineage differentiation, and strong anti-inflammatory features. In the present study, immunoregulatory and glandular tissue regeneration effects of the dental follicle (DF)MSCs in Sjögren’s Syndrome (SS) were investigated. Methods Dental follicle (DF) tissues were obtained from healthy individuals during tooth extraction, tissues were digested enzymatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, it was reported that freshly prepared MSCs can differentiate into non-mesodermal cell types such as epithelial, hepatocyte, and renal tubular cells. 23,24 The data showed that lyophilized DF-MSCs can differentiate to epithelial cells after being transferred to the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was reported that freshly prepared MSCs can differentiate into non-mesodermal cell types such as epithelial, hepatocyte, and renal tubular cells. 23,24 The data showed that lyophilized DF-MSCs can differentiate to epithelial cells after being transferred to the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…Dental pulp-derived stem cells may improve Sjogren’s hyposecretion through the TGF-b/Smad pathway, and studies suggest it may be more effective than bone marrow MSCs [ 78 , 79 ]. Dental follicle MSC decreased inflammatory cell deposits and fibrosis in glandular tissue, and showed differentiation into glandular epithelial cells [ 80 ]. Human exfoliated deciduous teeth stem cells, which are from the cranial neural crest, secrete soluble programmed cell death ligand 1 (PD-L1) and alleviate gland inflammation and dryness in mice [ 81 ].…”
Section: On the Horizon: Mesenchymal Stem Cells Therapy And Exosomesmentioning
confidence: 99%
“…Over the past decade, cell-based therapies have been examined as potential therapeutic approaches for SS ( Khalili et al, 2014 ; Elghanam et al, 2017 ; Genç et al, 2022 ). A particularly promising therapeutic option is the use of mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%